2022
DOI: 10.1136/tobaccocontrol-2021-056846
|View full text |Cite
|
Sign up to set email alerts
|

Differential price responses for tobacco consumption: implications for tax incidence

Abstract: Increasing tobacco taxes is considered the most effective an cost-effective policy to reduce tobacco consumption. However, a common objection to tobacco taxes is that they tend to rely disproportionately on the poorest individuals since less affluent smokers incur proportionately greater expenditures on cigarettes compared with more affluent smokers. Such objections usually assume that all smokers throughout the income distribution react similarly to an increase in tobacco prices. But, if less affluent smokers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
(40 reference statements)
2
9
0
Order By: Relevance
“…The price elasticities are in line with estimates for South Africa and other low-income and middle-income countries 19 20. It has been shown that smokers of cheaper brands are more sensitive to price increases than smokers of more expensive brands 21. For this reason, we assume larger (absolute) price elasticities for the cheaper segments than for more expensive segments.…”
Section: Scenario Analysissupporting
confidence: 76%
See 1 more Smart Citation
“…The price elasticities are in line with estimates for South Africa and other low-income and middle-income countries 19 20. It has been shown that smokers of cheaper brands are more sensitive to price increases than smokers of more expensive brands 21. For this reason, we assume larger (absolute) price elasticities for the cheaper segments than for more expensive segments.…”
Section: Scenario Analysissupporting
confidence: 76%
“…19 20 It has been shown that smokers of cheaper brands are more sensitive to price increases than smokers of more expensive brands. 21 For this reason, we assume larger (absolute) price elasticities for the cheaper segments than for more expensive segments. In addition, evidence suggests that some smokers switch to cheaper brands when their brand becomes more expensive.…”
Section: Scenario Analysismentioning
confidence: 99%
“…Based on Cicowiez, Sadoulet and de Janvry, Dimaranan and Muhammad et al, we define this value as follows: the value-added elasticities of substitution are in the range of 0.20-0.95, the Armington and Constant-Elasticity-of-Transformation (CET) elasticities are both in the range of 0.9-2.0 and the own price elasticities for household consumption demand are in the range of 0.4-1.0. [16][17][18][19] Most importantly, we calibrate GEM-Core Argentina under the assumption that the own price elasticity of tobacco product consumption is 0.6, as reported in Cruces et al 6 Table 1 describes the sectoral structure of Argentina's economy, for 2018, in terms of the distribution of value added, employment, exports and imports. It can be observed that tobacco-related activities (growing or primary production and manufacturing of tobacco products) represent a small share of the Argentine economy.…”
Section: Original Researchmentioning
confidence: 99%
“…4 Along these lines, Argentina had increased the overall tax burden on tobacco products (ie, cigarettes) from 69% in 2014 to 76% in 2018. 5 Second, the first objection on the eventual regressivity of raising tobacco taxes has recently been questioned by Cruces et al 6 We build a computable general equilibrium (CGE) model of the Argentine economy focused on the tobacco sector. In line with recent changes to the tobacco taxation, we simulate a 15 percentage point increase in the internal tax on cigarettes.…”
Section: Introductionmentioning
confidence: 99%
“…The papers included in this supplement span the regions of Asia, Latin America, and Southeastern Europe. The research focuses on consumer responses to cigarette price increases (Divino et al, 14 Nguyen et al, 15 Vladisavljevic et al 16 ) as well as their distributional impacts (Cruces et al, 17 Gligorić et al, 18 Divino et al, 19 Cizmovic et al, 20 Nguyen et al 15 ). Two papers analyse tax leakages along the tobacco supply chain: Vladisavljevic et al 16 use data from a primary survey in the Southeastern European region to analyse determinants of tobacco tax evasion and Drope et al examine the regional implications of the tobacco value chain in Paraguay.…”
Section: Editorialmentioning
confidence: 99%